Manifestasi Neurologis pada Pasien Covid-19 di Rumah Sakit Darurat Covid-19 Wisma Atlet Kemayoran Indonesia - Rakhmawati, Nurul; Bantolo, Suryo; Wijaya, Putri Bella; Khairunissa, Khalida; Alya, Tanissa Rizky; Jennyca, Putri; Rachmadani, Salma Dhiya; Dinno, Dinno (PERDOSNI, 2023)
Introduction: Coronavirus Disease 2019 (COVID-19) is a global disease with a high mortality rate. In Indonesia, the mortality rate has significantly increased, accompanied by various manifestations, including neurological symptoms. Aim: We aim to assess the clinical characteristics, including common symptoms and neurological manifestations, of COVID-19 patients at the COVID-19 National Emergency Hospital, Wisma Atlet Kemayoran. Methods: This study used a descriptive observational method with a cross-sectional design at the COVID-19 National Emergency Hospital, Wisma Atlet Kemayoran, Indonesia. Data were collected from June 2021 to February 2022, focusing on patients’ age, sex, comorbidities, severity degree, common symptoms, and neurological symptoms. Results: Among 599 patients, 63.8% were aged below 50, 53.1% were female, and 34.8% had hypertension. Mild symptoms were noted in 71.1% of cases, primarily cough (38.7%), while anosmia prevailed as the most common neurological symptom (33.2%). Chi-Square analysis highlighted significant associations between COVID-19 severity and variables like age, sex, pregnancy, comorbidities, and symptoms. Cough, runny nose, shortness of breath, fever, and appetite loss were linked to severity. Neurological symptoms, including anosmia, headache, and loss of consciousness, correlated with COVID-19 severity. Severe cases exhibited a heightened likelihood of central nervous system symptoms (p < 0.001) but a reduced chance of peripheral nervous system symptoms (p < 0.001). Discussions: In summary, age, sex, comorbidities, and various symptoms demonstrated significant relationships with COVID-19 severity, impacting both nervous system categories. The findings indicate that COVID-19 leads to diverse clinical presentations, ranging from mild to moderate, and contributes to numerous deaths. Keywords: common manifestation, COVID-19, neurological manifestation, SARS-COV 2, severity degree